The Role of Conferences on the Pathway to Academic Impact: Evidence from a Natural Experiment - Fernanda L. L. de Leon; Ben McQuillin (University of Kent, School of Economics, 2014)
This paper provides evidence for the role of conferences in generating visibility for academic work, using a 'natural experiment': the last-minute cancellation - due to 'Hurricane Isaac' - of the 2012 American Political Science Association (APSA) Annual Meeting. We assembled a dataset containing outcomes of 15,624 articles scheduled to be presented between 2009 and 2012 at the APSA meetings or at a comparator annual conference (that of the Midwest Political Science Association). Our estimates are quantified in difference-in-differences analyses: First using the comparator meetings as a control, then exploiting heterogeneity in a measure of session attendance, within the APSA meetings. We observe significant 'conference effects': on average, articles gain 17-26 downloads in the 15 months after being presented in a conference. The effects are larger for papers authored by scholars affiliated to lower tier universities and scholars in the early stages of their career. Our findings are robust to several tests.
Keywords: O39; I23; L38; 330; effects of conferences; diffusion of scientific knowledge